Maldives : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, outlook, and risks of Maldives' economy. Maldives living standards have risen to middle-income levels over the past two decades driven by tourism development. The country's geography creates fiscal challenges, and the economy has faced persistent fiscal deficits over the past decade. The economy is highly exposed to climate change, a fact that further adds to fiscal costs. The real economy outperformed its peers in the past few years, but tourism slowed last year. Public debt is high and on a rising trajectory. A detailed national development strategy would ensure that investment plans are well coordinated and bring about bigger growth dividends.